Association between SMAD3 gene rs12901499 polymorphism and knee osteoarthritis in a Chinese population. Issue 5 (8th January 2018) - Zhang, Li; Zhang, Limin; Zhang, Haiqin; Wang, Wenjun; Zhao, You
Abstract : Background: Many studies have revealed that transforming growth factor‐beta (TGF‐β) signals play important roles in maintaining normal status of articular cartilage in human osteoarthritis (OA). However, SMAD3 had inhibitory effect on TGF‐β‐induced chondrocyte maturation. Method: To evaluate the association of SMAD3 genetic variants with the risk of knee OA, we conducted this hospital‐based case‐control study involving 350 knee patients with OA and 400 controls in a Chinese population. Genotyping was performed using a custom‐by‐design 48‐Plex single‐nucleotide polymorphism (SNP) Scan ™ Kit. Results: Our results indicate that the GG genotype of rs12901499 could decrease the risk of knee OA compared to AA genotype. However, stratified analyses by sex and age did not obtain positive findings with regard to the association between rs12901499 polymorphism and knee OA risk. Conclusion: In conclusion, SMAD3 rs12901499 polymorphism may be involved in the development of knee OA. Larger studies with more diverse ethnic populations are needed to confirm these results.